Case Report: 3D-Printed Prosthesis for Limb Salvage and Joint Preservation After Tibial Sarcoma Resection - Guo, Zehao; Zhang, Ran; Que, Yukang; Hu, Bo; Xu, Shenglin; Hu, Yong (Frontiers in Surgery, 2022)
Introduction: Reconstruction of massive tibial defects in ankle joint-preserving surgery remains challenging though biological and prosthetic methods have been attempted. We surgically treated a patient with only 18 mm distal tibia remaining and reconstructed with a unique three-dimensional printed prosthesis. Case presentation, intervention, and outcomes: A 36-year-old male presented to our clinic with complaints of gradually swelling left calf and palpable painless mass for five months. Imageological exam indicated a lesion spanning the entire length of the tibia and surrounding the vascular plexus. Diagnosis of chondrosarcoma was confirmed by biopsy. Amputation was initially recommended but rejected, thus a novel one-step limb-salvage procedure was performed. After en-bloc tumor resection and blood supply rebuilding, a customized, three-dimensional printed prosthesis with porous interface was fixed that connected the tumor knee prosthesis and distal ultra-small bone segment. During a sixteen-month follow-up, no soft tissue or prosthesis related complications occurred. The patient was alive with no sign of recurrence or metastasis. Walking ability and full tibiotalar range of motion were preserved. Conclusions: Custom-made, three-dimensional printed prosthesis manifested excellent mechanical stability during the follow-up in this joint-preserving surgery. Further investigation of the durability and rate of long-term complications is needed to introduce to routine clinical practice.